NADPH Oxidase and Neurodegeneration - S. Hernandes, Marina; R.G. Britto, Luiz (Current Neuropharmacology, 2012)
NADPH oxidase (Nox) is a unique, multi-protein, electron transport system that produces large amounts of superoxide via the reduction of molecular oxygen. Nox-derived reactive oxygen species (ROS) are known to be involved in a variety of physiological processes, including host defense and signal transduction. However, over the past decade, the involvement of (Nox)-dependent oxidative stress in the pathophysiology of several neurodegenerative diseases has been increasingly recognized. ROS produced by Nox proteins contribute to neurodegenerative diseases through distinct mechanisms, such as oxidation of DNA, proteins, lipids, amino acids and metals, in addition to activation of redoxsensitive signaling pathways. In this review, we discuss the recent literature on Nox involvement in neurodegeneration, focusing on Parkinson and Alzheimer diseases.
Keywords: Nox enzymes